Porcine OGN and ASPN: mapping, polymorphisms and use for quantitative trait loci identification for growth and carcass traits in a Meishan x Piétrain intercross - Stratil, A; Van Poucke, M; Bartenschlager, H; Knoll, A; Yerle, M; Peelman, L J; Kopecný, M; Geldermann, H (Animal genetics, 2006)
The porcine orthologues of human chromosome HSA9q22.31 genes osteoglycin (OGN) and asporin (ASPN) were mapped to porcine chromosome SSC3 using linkage analysis and a somatic cell hybrid panel. This mapping was refined to SSC3q11 using fluorescence in situ hybridization. These results confirm the existence of a small conserved synteny group between SSC3 and HSA9. Polymorphisms were revealed in both genes, including a pentanucleotide microsatellite (SCZ003) in OGN and two single nucleotide polymorphisms (AM181682.1:g.780G>T and AM181682.1:g.825T>C) in ASPN. The two genes were included in a set of markers for quantitative trait loci (QTL) mapping on SSC3 in the Hohenheim Meishan x Piétrain F2 family. Major QTL for growth and carcass traits were centred in the ASPN-SW902 region.
Keywords: Glycoproteins; mezibuněčné signální peptidy a proteiny; lokus kvantitativního znaku; jednonukleotidový polymorfismus; syntenie; křížení genetické; mikrosatelitní repetice; Crosses, Genetic; Synteny; Intercellular Signaling Peptides and Proteins; proteoglykany; Microsatellite Repeats; Proteoglycans; Quantitative Trait Loci; Swine; zvířata; Humans; mapování chromozomů; Chromosome Mapping; prasata; glykoproteiny; lidé; Polymorphism, Single Nucleotide; Animals